Low-power artificial intelligence based sensors for wireless sensor network applications = Energooszczędne sensory bazujące na sztucznej inteligencji do zastosowań w sieciach sensorów bezprzewodowych - Turchan, Krzysztof; Michta, Emil; Piotrowski, Krzysztof (Zielona Góra: Uniwersytet Zielonogórski, Instytut Metrologii, Elektroniki i Informatyki)
This work describes the progress towards creating a framework for applying AI techniques on low- power sensor nodes. The aim of the approach is to make use of the AI operations on the nodes to allow moving the data processing as close as possible to the place the data is collected. This requires the processing to be low power but reliable, since the raw data will not be transferred from the source node.
Keywords: komputeryzacja; przyrządy pomiarowe; informatyka; technologie informacyjne